Analisis Kualitas Pelayanan Terhadap Kepuasan Pelanggan Asinan Buah Campur Al Markaz - Udin, Dindah Nur Safira P.U; Tenri S.P Dipoatmodjo; Muh. Ilham Wardhana; Romansyah Sahabuddin; Burhanuddin (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to (1) determine the effect of physical evidence on customer satisfaction, (2) knowing the effect of reliability on satisfaction consumers, (3) knowing the effect of guarantees on consumer satisfaction, and (4) determine the effect of responsiveness on consumer satisfaction. (5) Define the effect of empathy on consumer satisfaction, and (6) determine how physical evidence, reliability, assurance, responsiveness, and empathy all together affect consumer satisfaction Al Markaz Mixed Pickled Fruit on the Street Ranggong No. 8 Makassar City. The sample size of this study was 70 people. Research findings on physical evidence variables have no significant effect on consumer satisfaction with t-table < t count, namely -314 < 1.669. With t-table > t-count 1.759 > 1.669 then the reliability variable has a positive effect significant to customer satisfaction. With an it-table value of 0.505 <1.669 then the guarantee variable has no significant effect on customer satisfaction. With the value of t-table < t-count 0.540 < 1.669 the responsiveness variable is not significant effect on consumer satisfaction. With the t-table value > t count, namely 1.901 > 1.669, the empathy variable has a significant effect on customer satisfaction. This study shows that the variable evidence physicality, reliability, assurance, responsiveness and empathy are simultaneously influential significant effect on consumer satisfaction on Mixed Pickled Fruit Al Markaz Di Jalan Ranggong No. 8 Makassar City, proven by F test count 5.030 with probability value of 0.001 is smaller than the value of 0.005